PRAKTIK KAWIN LARI (PARU DHEKO) PADA REMAJA PEREMPUAN SMA DI DESA RAPORENDU DUSUN NUMBA BESAR KECAMATAN NANGAPANDA KABUPATEN ENDE - Sasmita, Anggun; Manafe, Jacklin Stefany; Ndandara, Aelshtri; Perangin Angin, Imanta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Practice of Kawin Lari (Paru Dheko) Among High School Adolescents in Raporendu Village, Numba Besar Hamlet, Nangapanda District, Ende Regency. This research is motivated by the increasing number of kawin lari (paru dheko) cases committed by high school adolescents in Raporendu Village, Numba Besar Hamlet, Ende Regency, with a total of 12 cases recorded between 2022 and 2024. Practically, this research is expected to serve as a reference for the community in reducing the incidence of kawin lari, while theoretically it contributes to sociological studies on social deviance in traditional societies. This study applies the Theory of Anomie by Emile Durkheim and Robert K. Merton, which explains social strain that arises when there is a mismatch between culturally defined goals and the legitimate means to achieve them. The research uses a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. Informants include 12 adolescent perpetrators of kawin lari, 6 parents, a traditional leader, a community leader, and a village official. The results show that the practice of (paru dheko) factors of pregnancy outside marriage, parental prohibitions and family conflict, economic factors and high dowry, emotional impulses and romantic relationships, peer influence, weakening social control, influence of social media, and the weak role of social institutions. From the perspective of Anomie Theory, kawin lari represents an innovative adaptation to social strain arising from adolescents' inability to meet cultural and normative expectations, especially related to family approval and traditional bridewealth requirements. The study also reveals that weakened social control, shifting values among youth, and lack of economic readiness contribute significantly to the persistence of kawin lari practices in the community.